PENGENDALIAN DAN PENGAWASAN PINTU AIR SUNGAI OTOMATIS BERBASIS SMS - Fitriady; Rahmad Sadli; Ma’ruf Fauzan (J-Innovation, 2016)
The prototype of automation and supervision of water river gate is designed to control and supervise the gate when the river floods the drain. The gate would open and close automatically when the river is overflow hence flood the community’s drain. This can anticipate flooding disaster in community livelihood. This automation using probe level sensor to measure water level and DC motor as drive machine to open/close gate. The microcontroller that used as a controller is Arduino UNO. The full open and full close position of drain gate indicated by active upper and lower limit switch. In order to send information of water levels and gate positions, GSM SIM900A module were used in this research as communication technology to send SMS text to gate operator.